2012
DOI: 10.1016/j.pmrj.2012.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of First Metatarsophalangeal Joint Injections for Sesamoid Disorders: A Cadaveric Investigation

Abstract: Accurate first MTPJ injections reliably deliver latex to the articular surfaces of the metatarsosesamoid articulations. Clinicians administering diagnostic or therapeutic injections for patients with sesamoid disorders should consider injecting the first MTPJ as an alternative to direct metatarsosesamoid articulation injections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…Three studies (two with level 2 evidence71 83 and one with level 3 evidence52) found 100% accuracy for USGI of the MTP joints with one of the three52 noting poor accuracy (0% accurate) with LMGI.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Three studies (two with level 2 evidence71 83 and one with level 3 evidence52) found 100% accuracy for USGI of the MTP joints with one of the three52 noting poor accuracy (0% accurate) with LMGI.…”
Section: Resultsmentioning
confidence: 98%
“…A small majority of these studies (5/9 (56%))31 66 71 82 83 evaluated injections into a single type of small joint (eg, metacarpophalangeal (MCP) joint), while the remainder (4/9 (44%))16 26 52 81 evaluated injections into multiple small joints. Sixty-seven per cent (6/9)16 26 31 52 81 82 of the studies assessed small joint injections in the hands and 56% (5/9)16 52 66 71 83 evaluated small foot joint injections. Of those studies assessing hand procedures, three studies (50%) included the carpometacarpal (CMC) joint,26 52 82 two (33%) the PIP joints52 81 and one (17%)26 the distal interphalangeal (IP) joints.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Iliopsoas tendon and bursa [90] Intra-articular hip joint [91] Piriformis injection [92] Knee Intra-articular knee [93] Baker's cyst aspiration [94] Pes anserine bursa [95] Foot/ankle Subtalar/tibiotalar/sinus tarsi [96] Retrocalcaneal bursa [97] Plantar fascia [98] Metatarsophalangeal joint/sesamoid disorders [99] Interdigital neuroma [100] ongoing studies are needed to assess clinical efficacy, the role of ultrasound in the emerging field of bioregenerative medicine appears crucial.…”
Section: Hipmentioning
confidence: 99%